2D simulation and experimental study of a horn influencing on an open-air traveling-wave thermoacoustic generator. (November 2022) - Wu, Dianwei; Xie, Xiujuan; Yang, Shaoqi
Abstract: In this paper, 2D CFD simulation and experimental study of a horn influencing on an open-air traveling-wave thermoacoustic generator were carried out. A 2D simulated model of open-air traveling-wave thermoacoustic generator with a diameter of 6 m external space is developed. The dynamic onset process, acoustic field distribution, acoustic power distribution, and time-averaged mass flow with and without horn at the open end are obtained and discussed. Nonlinear effects at the open end including the pressure waveform, FFT pressure spectra, pressure contours and velocity streamlines diagrams at different moments are analyzed. The simulated results demonstrate that the horn can significantly affect the air suction process at the opening and increase the oscillating pressure inside the thermoacoustic generator. Furthermore, the experimental results are compared with the 2D simulated results. The deviation range is between 2%–25%, which verifies the availability of 2D simulated model to analyze the flow and energy fields, nonlinear effect and dynamic process of thermoacoustic generator.